2013
DOI: 10.1007/978-1-4614-6093-0_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Effects of Taurine and Thiotaurine on Alterations of the Cellular Redox Status and Activities of Antioxidant and Glutathione-Related Enzymes by Acetaminophen in the Rat

Abstract: The present study was carried out to ascertain the impact of replacing the sulfonate group of TAU with thiosulfonate, as present in thiotaurine (TTAU), on the protective actions of TAU against hepatocellular damage and biochemical alterations related to oxidative stress and glutathione redox cycling, synthesis, and utilization caused by a high dose of acetaminophen (APAP). To this end, male Sprague-Dawley rats, 225-250 g, were intraperitoneally treated with a 2.4 mmol/kg dose of TAU (or TTAU), followed 30 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…In addition to depleting intrahepatic GSH, APAP seems to decrease the activity of anti-oxidant enzymes (SOD, CAT, GPx), as well as of enzymes involved in glutathione redox cycling (glutathione reductase, GR), utilization (glutathione S-transferase, GST) and synthesis (gamma-glutamylcysteine synthetase) ( 237 ). In this context, taurine has been shown to improve the effects of APAP on both oxidative stress and glutathione redox metabolism ( 238 ). Taurine administered at a dose of 2.4 mmol/kg for 30 min following administration of 800 mg/kg APAP appeared to successfully alleviate both DNA damage signals and oxidative indices ( 238 ).…”
Section: The Anti-oxidant Efficacy Of Taurine Against Hepatic- Associated Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to depleting intrahepatic GSH, APAP seems to decrease the activity of anti-oxidant enzymes (SOD, CAT, GPx), as well as of enzymes involved in glutathione redox cycling (glutathione reductase, GR), utilization (glutathione S-transferase, GST) and synthesis (gamma-glutamylcysteine synthetase) ( 237 ). In this context, taurine has been shown to improve the effects of APAP on both oxidative stress and glutathione redox metabolism ( 238 ). Taurine administered at a dose of 2.4 mmol/kg for 30 min following administration of 800 mg/kg APAP appeared to successfully alleviate both DNA damage signals and oxidative indices ( 238 ).…”
Section: The Anti-oxidant Efficacy Of Taurine Against Hepatic- Associated Stressmentioning
confidence: 99%
“…In this context, taurine has been shown to improve the effects of APAP on both oxidative stress and glutathione redox metabolism ( 238 ). Taurine administered at a dose of 2.4 mmol/kg for 30 min following administration of 800 mg/kg APAP appeared to successfully alleviate both DNA damage signals and oxidative indices ( 238 ). This was achieved by i) reducing MDA formation, ii) regulating glutathione cycling-utilization-synthesis cycle, iii) increasing the already reduced glutathione to glutathione disulfide (GSH/GSSG) ratio and iv) increasing the activity of all anti-oxidant enzymes ( 238 ).…”
Section: The Anti-oxidant Efficacy Of Taurine Against Hepatic- Associated Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiotaurine possesses antioxidant and regulatory properties. Interestingly, a previous study had shown that the protective, antioxidant action of thiotaurine was stronger than that of taurine (Acharya & Lau-Cam, 2013). It was probably connected with presence of a thiosulfonate group in thiotaurine.…”
Section: Thiotaurine As a Sulfane Sulfur Compoundmentioning
confidence: 94%
“…Thus far, little is known about the pharmacokinetics of taurine after oral administration. Such information is essential if a regimen for administration of this agent as a nutraceutic in enteral diets or as therapeutic substance is designed – for example in treating the adverse effects of nickel in the nervous system ( 23 ) or after paracetamol poisoning ( 24 , 25 ) . A review of the literature revealed only very few reports concerning the pharmacokinetics of taurine.…”
mentioning
confidence: 99%